First Report of Biodiversity Enrichment through Introduction of Tuber Yielding Crops in the Natural forest (an Inspiring Model of Participatory Management) - Das, Nilanjana; Prasad, B. K.; Manna, G. B.; Chattopadhyay, R. N. (Indian Forester, 2002)
No abstract